2001
DOI: 10.1046/j.1365-3156.2001.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to development of Mycobacterium ulcerans disease: review of possible risk factors

Abstract: SummaryMycobacterium ulcerans disease, also known as Buruli ulcer (BU), is a disease of subcutaneous fat tissue. BU is prevalent in riverine and swamp areas of the tropical zone in Africa, Asia and South America, and a few scattered foci in Australia. The mode of transmission of M. ulcerans has not been fully elucidated, but inoculation into the subcutaneous tissues probably occurs through penetrating skin trauma. BU has not been linked with HIV infection. Antimycobacterial drug treatment is ineffective, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 80 publications
9
50
0
Order By: Relevance
“…On the other hand, in a more recent study, Phillips et al (27), using a higher number of patients, reported a strong expression of IFN-g in both nodular and ulcerative lesions. Also in line with our findings, supporting therefore the existence of protective cellular-mediated immune and delayed-type hypersensitivity responses, associated with IFN-g production in the context of Th1 responses, when BU disease progresses to healing, granuloma formation occurs (3,46,(53)(54)(55), and the positivity of the Burulin skin test increases (56)(57)(58). In addition, BCG vaccination was found to protect humans against BU osteomyelitis (59), and BCG or a DNA vaccine encoding Ag85A from BCG confer some degree of protection against M. ulcerans experimental infections (60,61).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, in a more recent study, Phillips et al (27), using a higher number of patients, reported a strong expression of IFN-g in both nodular and ulcerative lesions. Also in line with our findings, supporting therefore the existence of protective cellular-mediated immune and delayed-type hypersensitivity responses, associated with IFN-g production in the context of Th1 responses, when BU disease progresses to healing, granuloma formation occurs (3,46,(53)(54)(55), and the positivity of the Burulin skin test increases (56)(57)(58). In addition, BCG vaccination was found to protect humans against BU osteomyelitis (59), and BCG or a DNA vaccine encoding Ag85A from BCG confer some degree of protection against M. ulcerans experimental infections (60,61).…”
Section: Discussionsupporting
confidence: 91%
“…In the ulcerative non-granulomatous lesions it was common that bacteria were overlying cells, but in some peripheral areas distant to necrosis we found fewer and dispersed bacilli; in these areas some macrophages showed well-defined intracellular AFB, suggesting real phagocytosed mycobacteria. This observation is in agreement with recent in vitro studies which demonstrated that occasional macrophages can be infected by M. ulcerans [23], and with the concept that M. ulcerans has an intracellular phase that is necessary for the induction of a Th1 immune response [24,25]. It has been demonstrated recently that mycolactone is anti-phagocytic, but macrophages can phagocytose M. ulcerans during early experimental infection and transport the bacilli to the regional lymph nodes [26].…”
Section: Discussionsupporting
confidence: 91%
“…As shown, in progressive murine infection by virulent M. ulcerans, such a switch is not fully completed. This observation correlates with the finding that progressive infection of the skin, disseminated disease, and osteomyelitis in BU patients were associated with an absence of granulomas in the infected areas (33,49,66). Conversely, with the noncytotoxic strain 5114, which is not virulent for mice and does not cause leukocyte death and necrosis of the subcutaneous tissue at any stage of infection, the acute neutrophilic profile of the cellular infiltrate gradually switches to a predominance of mononuclear cells and formation of granuloma-like structures.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, with the noncytotoxic strain 5114, which is not virulent for mice and does not cause leukocyte death and necrosis of the subcutaneous tissue at any stage of infection, the acute neutrophilic profile of the cellular infiltrate gradually switches to a predominance of mononuclear cells and formation of granuloma-like structures. Not surprisingly, this type of chronic response was observed in BU patients during the healing phase of disease (30,31,40,49,66,74).…”
Section: Discussionmentioning
confidence: 77%